Global burden of chronic kidney disease in adolescents and young adults, 1990–2019: a systematic analysis for the Global Burden of Disease Study 2019 - Sun, Ping; Ming, Xingyu; Song, Tiange; Chen, Yan; Yang, Xin; Sun, Zhaochen; Zheng, Xiaoxia; Tong, Luyao; Ma, Zhiwei; Wan, Zhengwei (Frontiers in Endocrinology, 2024)
Background The global status of chronic kidney disease (CKD) is underestimated, particularly the burden on adolescents and young adults (early-onset, aged 15–39). Objective We aim to investigate the pattern and trend of early-onset CKD from 1990 to 2019. Methods We analyzed age-specific rates of early-onset CKD incidence, death, and disability-adjusted life years (DALY) using Global Burden of Disease Study 2019 data. We examined the global, regional, national, gender-based, age group-based, and temporal changes of early-onset CKD burden from 1990 to 2019, as well as proportional DALY attributions of various risk factors. Results From 1990 to 2019, the global age-specific incidence rate (per 100,000 population) significantly increased from 25.04 (95% confidence interval 18.51, 31.65) to 32.21 (23.73, 40.81) for early-onset CKD. However, the global age-specific death rate significantly decreased from 2.96 (2.76, 3.15) to 2.86 (2.61, 3.11), and the age-specific DALY rate remained stable. Regarding sociodemographic indexes (SDI), countries with middle SDI had the highest incidence rates and the fastest increasing trends, while those with low and low-middle SDI experienced the highest death and DALY rates. Women had a generally higher age-specific incidence rate than men, whereas men showed higher age-specific death and DALY rates. In addition, the burdens of CKD increased with age among adolescents and young adults. Moreover, the main attributable risk factors for DALY of early-onset CKD were high systolic blood pressure (SBP), fasting plasma glucose (FPG), and body mass index (BMI). Conclusion The age-specific incidence rate of early-onset CKD increased significantly from 1990 to 2019, and the age-specific DALY rate remained stable. High SBP, high FPG, and high BMI were the primary risk factors. Targeted prevention and healthcare measures should be developed considering age, gender, and region.